The Effect of Plasma Arc Process Parameters on the Properties of Dissimilar AISI 1040/AISI 304 Steel Plate Welds - Kilic, Musa; Kirik, Ihsan; Celik, Ferkan; Orhan, Nuri (Carl Hanser Verlag, 2012)
In this study, 10 mm thick AISI 1040 and AISI 304 steel plates were welded in the butt position without pretreatment by plasma transferred arc (PTA) welding technique. Therefore, mechanical behaviour, microstructure, penetration depth and length were investigated. After welding, microstructural changes in the interface regions of the welded specimens were examined by scanning electron microscopy (SEM) and energy dispersive spectrometry (EDS). Micro-hardness as well as V-notch Charpy tests were performed to determine the mechanical properties of the welds. The influence of the welding parameters on the dimension and shape of the joints has been found out. From the results, it was derived that with the parameters used, a partly keyhole weld bead formed with a penetration depth of 10 mm and a width of 11 mm in butt position.